The effect of 6-week core stability training on core endurance and physical performance in professional rugby players: A randomized controlled pilot study - Senavirathna, Chamila S.; Mallawaarachchi , Anuja P.; Karunanayake, Aranjan L.; Gunawardena , Sampath (Asian Journal of Medical Sciences, 2021)
Background: Core stability training (CST) is used to enhance sports performance. The relationship between core endurance and physical performance in rugby players had not been evaluated before in Asia. Aims and Objectives: This study aims to determine the effects of a 6-week specific CST program on the core endurance and physical performances (speed, upper body power, lower body power, and agility) following a CST intervention in male rugby players. Materials and Methods: Professional rugby players (n=8, intervention and n=8, control) were randomly selected. Mean (SD) age, height and weight of intervention group were 25.25 (2.4) years, 1.64 (0.03) m, and 69.6 (14.9) kg, respectively. In the control group, corresponding values were 29.75 (4) years, 1.66 (0.04) m, and 72.3 (19.1) kg, respectively. Intervention group was trained CST sessions complementary to the usual physical training, 3 times/week for 6 weeks. The control group followed the usual physical training. Subjects were tested for four physical performances (using 40 m sprint, vertical jump, 3 kg medicine ball put, and agility T tests) and four core endurance tests (back extension, abdominal fatigue [AF], and left and right bridges). Results: AF, left bridge, right bridge, and total core endurance were significantly increased in the intervention group (P=0.028, P=0.006, P= 0.008, and P=0.001, respectively). Agility and AF were increased significantly in the control group (P=0.048, P=0.027). The right side bridge endurance (P=0.024) was significantly increased in the intervention group compared to the control group. Conclusion: The results suggest that the CST improves core endurance without improving physical performances in rugby players.